2006
DOI: 10.1073/pnas.0510254103
|View full text |Cite
|
Sign up to set email alerts
|

The G12 family of heterotrimeric G proteins promotes breast cancer invasion and metastasis

Abstract: Although the prognosis for patients with early-stage breast cancer has improved, the therapeutic options for patients with locally advanced and metastatic disease are limited. To improve the treatment of these patients, the molecular mechanisms underlying breast cancer invasion and metastasis must be understood. In this study, we report that signaling through the G12 family of heterotrimeric G proteins (G␣12 and G␣13) promotes breast cancer cell invasion. Moreover, we demonstrate that inhibition of G12 signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
193
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(210 citation statements)
references
References 35 publications
14
193
3
Order By: Relevance
“…The contraction at the trailing edge is mediated by the small GTPase RhoA (27). Recently, it has been shown that RhoA was activated by GPCR signaling, including those elicited by U46619, through G 12 heterotrimeric G proteins during invasion of cancer cells, including PC-3 (34,35). Our study suggests that TP can regulate cell migration and cytoskeleton reorganization through inducing cell contraction via activating RhoA.…”
Section: Resultsmentioning
confidence: 50%
“…The contraction at the trailing edge is mediated by the small GTPase RhoA (27). Recently, it has been shown that RhoA was activated by GPCR signaling, including those elicited by U46619, through G 12 heterotrimeric G proteins during invasion of cancer cells, including PC-3 (34,35). Our study suggests that TP can regulate cell migration and cytoskeleton reorganization through inducing cell contraction via activating RhoA.…”
Section: Resultsmentioning
confidence: 50%
“…The invasion and migration assays was performed (Kelly et al, 2006a;Kelly et al, 2006b) by using a 24-well transwell chamber with 8-um pore size polycarbonate membrane (Corning, USA) as recommended by the supplier. For invasion assay, the upper side of polycarbonate filter was coated with matrigel (30 ul, diluted in 1:3, BD, Biosciences).…”
Section: Cell Invasion and Migration Assaysmentioning
confidence: 99%
“…Interaction of SW480 and CT26 with ADAM10 stimulates RhoA activity As the interaction of Ga13 with RhoA leads to an increase in cell cortical tension as well as in disruption of plasma membrane-cortical actin, 22,23 we investigated whether the interaction of SW480 and CT26 cells with ADAM10Cys-EGFP or ADAM10-EGFP activates Rho small GTPase. To this end, we performed a GTP-RhoA pull-down assay.…”
Section: Adam10 and Cd81 Regulate Localization Of Gtp-binding A13mentioning
confidence: 99%